MEDIATISASI BELANJA ONLINE SHOP (SHOPEE) MELALUI TEKNOLOGI MEDIA - Fauzan Hidayatullah; Kadek Aryana Dwi Putra; Rosnani Abdul Rahman; Mulawarman Mulawarman (KAREBA : Jurnal Ilmu Komunikasi, 2021)
Technological developments increase people's income in the economic field with the internet, which can meet the community's needs in conducting buying and selling transactions practically via the internet. The many online shop businesses that offer various needs at affordable prices compared to supermarkets or malls, changes in shopping behavior through online shopping in the community. This research uses qualitative research with a literature study approach. The features possessed by online shops provide convenience for people who use them because they can find the items they need only through smartphones. In addition to offering comfort to the features it has, Shopee also often provides discounts, especially on certain days. Currently, people prefer to shop through online shops compared to traditional markets because there are services owned by online shops but cannot be found in traditional markets. Shopee is an online shop that pampers someone in shopping because of the COD facility or the goods delivery system. Consciously or unconsciously, people are currently subject to the rules owned by Shopee, because they have considered it a natural thing to make buying and selling transactions through an online shop (Shopee).